"Do not question authority": Examining team rules in national collegiate athletic association division I women`s basketball - Larsen, L. K.; Fisher, L. A.; Shigeno, T. C.; Bejar, M. P.; Madeson, M. N. (International Sport Coaching Journal, 2020)
While the policies National Collegiate Athletic Association (NCAA) athletic departments have in place regarding social media and drug abuse have been empirically investigated, research on the full battery of rules implemented by NCAA teams is scant. Therefore, the purpose of this study was to analyze the written team rules of 41 NCAA Division I women`s basketball teams to better understand the types of rules that are in place and to hypothesize the effects these rules might have on the development of an autonomy-supportive environment. Using Consensual Qualitative Research, the research team constructed seven domains with multiple categories to represent the data. The domains included the following: (a) program expectations, (b) controlled communication, (c) controlled relationships, (d) controlled appearance/attire, (e) controlled social behavior, (f) recommendations for optimal physical performance, and (g) academic expectation. Based on the results of this study, we conclude that NCAA Division I women`s basketball coaches use team rules as a tool for domination rather than a strategy for developing the autonomy of student-athletes. We offer practical suggestions for coach educators, coach developers, and coaches on best practices when creating team rules to develop an autonomy-supportive environment that strengthens organizational loyalty and improves the experiences of student-athletes.